(untitled) (Altre Modernità, 2017)
The man in the street’s attitude of mind towards dictionaries is that they are the true repositories of all the words in a language, and that they are both authoritative and objective – in short, dictionaries are perfect. By mainly referring to the early history of English mono- and bilingual lexicography, this essay explodes the myth of the perfect dictionary and shows that mistakes in dictionaries may profitably be discussed under two headings: lexicographical mistakes, i.e. vague or circular definitions and the so-called ghost words in monolingual dictionaries, and non-insertable equivalents in bilingual dictionaries; and socio-cultural mistakes, which are related to the often elusive impact of ideology on dictionary-making.